Understanding treatment delay: Perceived barriers preventing treatment-seeking for eating disorders. (March 2022) - Hamilton, Amber; Mitchison, Deborah; Basten, Christopher; Byrne, Susan; Goldstein, Mandy; Hay, Phillipa; Heruc, Gabriella; Thornton, Christopher; Touyz, Stephen
Objective: Only a small proportion of individuals with an eating disorder will receive targeted treatment for their illness. The aim of this study was to examine the length of delay to treatment-seeking and determine the barriers preventing earlier access and utilisation of eating disorder treatment for each diagnostic group – anorexia nervosa, bulimia nervosa, binge eating disorder and other specified feeding or eating disorder. Method: Participants were recruited as part of the TrEAT multi-phase consortium study. One hundred and nineteen Australians (13–60 years; 96.9% female) with eating disorders currently accessing outpatient treatment for their illness completed an online survey comprised of self-report measures of eating disorder severity, treatment delay and perceived barriers to treatment-seeking. The treating clinician for each participant also provided additional information (e.g. body mass index and diagnosis). Results: Overall, the average length of delay between onset of eating disorder symptoms and treatment-seeking was 5.28 years. Controlling for age, latency to treatment-seeking was significantly longer for individuals with bulimia nervosa and binge eating disorder compared to anorexia nervosa. However, when perceived barriers to treatment-seeking were investigated, there were no significant differences between the diagnostic groups in regard to the perceived barriers they experienced. Stigma was rated as the most impactful barrier for each diagnostic group. Conclusion: Findings suggest that individuals with eating disorders face substantial delays in accessing appropriate treatment and that latency to treatment-seeking is often magnified for counter-stereotypical eating disorder presentations. Further research is required to investigate other factors contributing to this delay.